A Content Analysis and Meta-Analysis on the Effects of Classcraft on Gamification Learning Experiences in terms of Learning Achievement and Motivation. (20th November 2021) - Zhang, Qi; Yu, Liheng; Yu, Zhonggen
Abstract : Classcraft has become an attractive gamification choice that turns classes into motivating and joyful role-playing experiences. Based on the content analysis and meta-analysis, this study aims to investigate the efficiency of Classcraft in terms of optimal gamification learning experiences associated with learning achievement and motivation. After the identification, screening, eligibility, and inclusion processes, we have found that learning achievement and motivation are significant factors conducive to optimal gamification learning. The meta-analysis based on STATA 15 has demonstrated that gamification platforms including Classcraft can similarly enhance learning achievement ( d  = 0.621, z  = 5.846, 95% CI [0.413, 0.829]) and motivation ( d  = 0.608, z  = 6.167, 95% CI [0.415, 0801]), suggesting that gamification platforms including Classcraft can create optimal learning experiences. Another content analysis has revealed that Classcraft involving gamified reward mechanics, interactive settings, and collaborative tasks can fulfil the conditions of optimal gamification learning experiences. The main conclusion is that Classcraft can efficiently create optimal gamification learning processes that can positively influence learning achievement and motivation. We have also discussed the potential reasons for the positive effects of gamification on learning achievement and motivation. Game implementation can reflect learners' preference for well-being based on continuity, interaction, and openness.